2022
DOI: 10.21274/ar-rehla.v2i2.5887
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Bibliometrik Pariwisata Halal Untuk Mengeksplorasi Determinan Daya Saing Destinasi Wisata

Abstract: Abstrak: Penelitian ini bertujuan untuk mengetahui peta perkembangan penelitian terkait pariwisata halal menggunakan pendekatan analisis bibliometrik. Penelitian ini juga mengidentifikasi berbagai indikator yang dapat digunakan sebagai faktor penentu daya saing destinasi wisata. Penelitian ini menggunakan pendekatan statistik deskriptif. Penelitian ini menggunakan metode bibliometrik yang digunakan untuk mengevaluasi data bibliografi, termasuk jumlah jurnal, jumlah penulis, jumlah artikel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Research conducted by Suryani et al, (2022) and Azmi et al, (2021) focused on halal cosmetics by mapping its development over ten years. Then, research by Cahyani et al, (2022) discussed halal tourism and research Anam (2022) which discussed halal food. Several previous studies did not focus on the halal industry globally but focused more on sub-sectors of the halal industry, even though the analysis used was the same, namely bibliometric analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Suryani et al, (2022) and Azmi et al, (2021) focused on halal cosmetics by mapping its development over ten years. Then, research by Cahyani et al, (2022) discussed halal tourism and research Anam (2022) which discussed halal food. Several previous studies did not focus on the halal industry globally but focused more on sub-sectors of the halal industry, even though the analysis used was the same, namely bibliometric analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Then, research conducted by Darmawati et al, (2023) used bibliometric analysis selected using criteria carried out in 2009-2022. While research by Suryani et al, (2022) and Azmi et al, (2021) focused on halal cosmetics by mapping its development over ten years, research by Cahyani et al, (2022) discussed halal tourism and research Anam (2022) which discussed halal food.…”
Section: Introductionmentioning
confidence: 99%
“…A bibliometric study of halal tourism found in keyword analysis that the main themes were halal tourism, intention to visit, honesty, halal food, accommodation, halal knowledge, halal certification, and tourism websites [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Each color that appears indicates a keyword cluster and the size of the circle indicates the number of times the keyword appears. Keywords that frequently appear in the document being analyzed are indicated by the size of the circle and letters that are getting bigger (Cahyani et al, 2022). This paper uses 24 articles and a total of 59 authors.…”
Section: Halal Food Smes Bibliometric Analysismentioning
confidence: 99%